"What happened? I played three notes and had 600,000 likes": rising Internet celebrities in China's digital music industry - Lu, Xiaoxiao (2024)
This thesis delves into an in-depth exploration of the transformative impact that Douyin, China's counterpart to TikTok, has had on the careers of musicians within the Chinese music industry. The central focus of this study revolves around wanghong (internet celebrity) music streamers on Douyin who have risen to prominence in the realm of Chinese social media. Through extensive ethnographic research, encompassing interviews, participant observations, and digital walkthroughs, this study provides detailed insights into how the lives and careers of wanghong musicians have evolved within the Douyin platform. It uncovers the strategies employed by these musicians in navigating Douyin's digital environment and underscores the significance of creativity, various monetization methods, and social connections in achieving both economic success and career growth within the digital market. Furthermore, this research unveils the distinctive digital ecosystem where musicians can leverage diverse monetization channels to sustain their digital careers within a democratic social media landscape of mass users' engagement. This thesis also sheds light on the phenomenon of digital collectivism in music consumption on comprehensive social media platforms like Douyin, where mass users organically contribute to the sustainability of the streamers' work. These insights within the digital ecosystem on the Douyin platform reveal new dynamics in cultural economics, challenging traditional notions that prioritize copyright protection within the digital music industry. While this study acknowledges certain limitations, it serves as a valuable resource to comprehend the profound influence that influential digital platforms exert on the broader cultural and creative industries.